IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGZAW UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN EKONOMI SMA NEGERI 35 HALMAHERA SELATAN - Iriani Lasaria; Sunarti Djoko; Faisal Y Habsyi (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2023)
The research design used in this is classroom action research. The subjects of the study were 27 students of class X. The purpose of this study was to determine the effectiveness of using the jigsaw cooperative model to improve student learning activity in economics subjects. Data collection techniques used observation, observation, tests and documentation. Data analysis was descriptive-narrative as a measure of the success of the learning improvement process. By implementing the jigsaw cooperative model, students who actively participate and students who are active observers can develop imagination, form group cohesiveness, students are not shy and hesitant to develop potential. Increased learning activity can be proven by an increase in quality in the affective domain through observation and tests before the action of 70-80 in cycle I, then in cycle II increased again to 72-82. While in the affective domain from cycle I 70-80 increased to 72-82 in cycle II. The purpose of this study was to determine the effectiveness of using the jigsaw cooperative model to improve student learning activity in economics subjects.